Is wounding aggression in zoo‐housed chimpanzees and ring‐tailed lemurs related to zoo visitor numbers?. Issue 3 (29th February 2016) - Hosey, Geoff; Melfi, Vicky; Formella, Isabel; Ward, Samantha J.; Tokarski, Marina; Brunger, Dave; Brice, Sara; Hill, Sonya P.
Abstract : Chimpanzees in laboratory colonies experience more wounds on weekdays than on weekends, which has been attributed to the increased number of people present during the week; thus, the presence of more people was interpreted as stressful. If this were also true for primates in zoos, where high human presence is a regular feature, this would clearly be of concern. Here we examine wounding rates in two primate species (chimpanzees Pan troglodytes and ring‐tailed lemurs Lemur catta ) at three different zoos, to determine whether they correlate with mean number of visitors to the zoo. Wounding data were obtained from a zoo electronic record keeping system (ZIMS™). The pattern of wounds did not correlate with mean gate numbers for those days for either species in any group. We conclude that there is no evidence that high visitor numbers result in increased woundings in these two species when housed in zoos. Zoo Biol. 35:205–209, 2016. © 2016 Wiley Periodicals, Inc.